2015
DOI: 10.3906/sag-1404-136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pioglitazone, quercetin, and hydroxy citric acid on vascular endothelial growth factor messenger RNA (VEGF mRNA) expression in experimentally induced nonalcoholic steatohepatitis (NASH)

Abstract: Background/aim: Vascular endothelial growth factor (VEGF) is associated with various ischemic and inflammatory diseases, and plays an important role in the development of liver fibrosis and hepatocarcinogenesis in nonalcoholic steatohepatitis (NASH). In this study, the comparative effect of pioglitazone, quercetin, and hydroxy citric acid on VEGF mRNA in experimentally induced NASH was investigated. Materials and methods:The experimental protocol consisted of five groups: control, NASH, NASH + pioglitazone, NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…EEGS treatment in HFD-treated rats exhibited significant suppression in expression of VEGF. This is consistent with previous observations Surapaneni et al (2015) who proved that quercetin downregulates VEGF expression more than hydroxy citric acid and pioglitazone in NASH rats model. Domitrović et al (2013) revealed the antioxidant, and antifibrotic prospect of rosmarinic acid in acute hepatic intoxication.…”
Section: Discussionsupporting
confidence: 93%
“…EEGS treatment in HFD-treated rats exhibited significant suppression in expression of VEGF. This is consistent with previous observations Surapaneni et al (2015) who proved that quercetin downregulates VEGF expression more than hydroxy citric acid and pioglitazone in NASH rats model. Domitrović et al (2013) revealed the antioxidant, and antifibrotic prospect of rosmarinic acid in acute hepatic intoxication.…”
Section: Discussionsupporting
confidence: 93%
“…Contrary to this, VEGF expression is suppressed by EEFS treatment in AD-treated rats. This corresponds to the observation of Surapaneni et al (2015) who described the role of quercetin in minimizing VEGF expression in AD-fed rats. Fan et al (2017) concluded the anti-inflammatory role of catechins in bowel disease.…”
Section: Discussionsupporting
confidence: 89%
“…Vascular endothelial growth factor (VEGF) has been found to play an important role in the development of liver fibrosis and liver neoplasms and may be inhibited by QE, as studied by Surapaneni et al . [ 96 ]…”
Section: Quercetin Liver Disease and Nafldmentioning
confidence: 99%